Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1063/1.4883957
|View full text |Cite
|
Sign up to set email alerts
|

Photo annealing effect on p-doped inverted organic solar cell

Abstract: We report the transient positive photo annealing effect in which over 600% boost of power conversion efficiency was observed in inverted organic photovoltaic devices (OPV) made from P3HT/PCBM by spray method, after 2 hrs of constant solar AM 1.5 irradiation at low temperature. This is opposite to usual photodegradation of OPV, and cannot be explained by thermal activation alone since the mere temperature effect could only account for 30% of the enhancement. We have investigated the temperature dependence, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…We attribute this decrease in the fluorescence intensity to static quenching upon reorientation of the chromophores during fluorescence detection. This reorientation from random molecule orientations after drop casting to energetically more favorable supramolecular geometries is supposed to be driven by thermalized absorbed energy, i.e., by photoannealing . The quenching might be due to self-quenching or unfavorable rotation of the TDVs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We attribute this decrease in the fluorescence intensity to static quenching upon reorientation of the chromophores during fluorescence detection. This reorientation from random molecule orientations after drop casting to energetically more favorable supramolecular geometries is supposed to be driven by thermalized absorbed energy, i.e., by photoannealing . The quenching might be due to self-quenching or unfavorable rotation of the TDVs.…”
Section: Resultsmentioning
confidence: 99%
“…This reorientation from random molecule orientations after drop casting to energetically more favorable supramolecular geometries is supposed to be driven by thermalized absorbed energy, i.e., by photoannealing. 70 The quenching might be due to self-quenching or unfavorable rotation of the TDVs. Thiazole 5.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In another inverted heterojunction OPV, reported by Lafalce et al, 38 a slow drift in the dark I−V curve of the device was observed when the device was exposed to air. In the absence of the ZnO layer in their device, the change was related to the photodoping effect of the P3HT by reacting with oxygen and affecting the charge in the space charge region.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…In addition, the transition from the rectifying property to the linear response and vanishing the hysteresis effect indicate that, at one of the interfaces, there was an energy barrier in the dark, and the energy barrier was gradually reduced upon illumination. Although, to the best of our knowledge, the optical effect of switching between the rectifying and linear characteristics has not been reported yet, the change in the I–V curve with large time constants have been experienced before in several OPV devices. Recently, Wilken et al observed a gradual reduction of the forward current with a time constant in the order of 30 min in an ITO/ZnO nanoparticles/P3HT:PCBM/PEDOT device after exposing to ambient air. The change in the response was explained through adsorption and desorption of oxygen at the ZnO surface adjacent to the organic layer, which resulted in change of the band bending in the ZnO layer (surface state charging).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation